2008
DOI: 10.1038/npp.2008.67
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Dendritic Spine Density in Auditory Cortex of Subjects with Schizophrenia

Abstract: We have previously identified reductions in mean pyramidal cell somal volume in deep layer 3 of BA 41 and 42 and reduced axon terminal density in deep layer 3 of BA 41. In other brain regions demonstrating similar deficits, reduced dendritic spine density has also been identified, leading us to hypothesize that dendritic spine density would also be reduced in BA 41 and 42. Because dendritic spines and their excitatory inputs are regulated in tandem, we further hypothesized that spine density would be correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
221
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(248 citation statements)
references
References 116 publications
23
221
2
1
Order By: Relevance
“…Such a reduction could certainly account for the differences reported here, especially with respect to reduced cortical source strength. Even more recently this same group has reported a reduction in dendritic spine density in both primary and associative auditory cortices (Sweet, et al, 2008) in the same group of subjects. The SSR has been postulated to represent the activation of a resonant loop between the auditory cortex and the thalamus (e.g., Ribary et al, 1991), and hence a deficit in the pyramidal cell, and/or dendritic spine density, should result in smaller evoked cortical strength estimates as observed here.…”
Section: Discussionmentioning
confidence: 81%
“…Such a reduction could certainly account for the differences reported here, especially with respect to reduced cortical source strength. Even more recently this same group has reported a reduction in dendritic spine density in both primary and associative auditory cortices (Sweet, et al, 2008) in the same group of subjects. The SSR has been postulated to represent the activation of a resonant loop between the auditory cortex and the thalamus (e.g., Ribary et al, 1991), and hence a deficit in the pyramidal cell, and/or dendritic spine density, should result in smaller evoked cortical strength estimates as observed here.…”
Section: Discussionmentioning
confidence: 81%
“…47 Reduced somal size of pyramidal neurons and reduced density of dendrites and axon terminals in cortical layer 3 has been demonstrated in the primary auditory cortex and the auditory association cortex in schizophrenia. [48][49][50] Pyramidal neurons in layer 3 in the sensory cortex are involved in feedforwarding sensory signals to higher cortical areas. Sweet et al 49 suggested that the abnormalities observed from postmortem studies may give rise to impaired precision of early auditory processing.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] Pyramidal neurons in layer 3 in the sensory cortex are involved in feedforwarding sensory signals to higher cortical areas. Sweet et al 49 suggested that the abnormalities observed from postmortem studies may give rise to impaired precision of early auditory processing. 51 Deficits in auditory processing, such as reduced tone matching abilities or abnormalities in electroencephalographic activity during early phases of auditory processing are evident in schizophrenia, and may contribute to mechanisms leading to AH.…”
Section: Discussionmentioning
confidence: 99%
“…Images containing monkey sections were acquired on an Olympus IX81 microscope with a spinning disk confocal unit and a Hamamatsu EM-CCD digital camera at 60× magnification. Ten image stacks (512 × 512 pixel; 0.25 μm z step) in layer 4, defined as 50-60% of the pia-to-white matter distance, per each section were selected using a previously published method for systematic random sampling (33). The mean numbers of PVimmunoreactive neurons sampled in the same volume of tissue did not differ between age groups (t 11 = 0.06, P = 0.952).…”
Section: Methodsmentioning
confidence: 99%